Functional food components, intestinal permeability and inflammatory markers in patients with inflammatory bowel disease - Lacerda, Joana Franco (2021)
Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).